PENDIDIKAN ACTIVE NON-VIOLENCE PERSPEKTIF AL-QUR??AN (KAJIAN TEMATIK TERHADAP AYAT-AYAT TOLERANSI DALAM AL-QUR??AN) - Azzah Nor Laila; Ahmad Saefudin (Tarbawi : Jurnal Pendidikan Islam, 2015)
This article is concern on spirit of active non violence education, which is based on Qur??anic verses. This article use thematic method in order to understanding content of Qur??an about this topic. That way, it may change negative strereotype and intolerance behaviour which were correlated with religion??s doctrine. Qur??an as a holy book for moslems containing of education values active non violence. One of them is tolerance. Besides, it becomes way of life, and important thing for every moslem to realize tolerance in society. Based on Qur??anic verses, there are many teachings that related to tolerance in religion such as freedom of believing, allow of greeting to other believers, and say congratulation of great day to other believers religion. In social aspect, everyone can compete in this world to reach a success and do charity selflessly. In cultural aspect, Qur??an teaches the necessity of positive thinking, no condemn, and avoid suudhan or prejudice. In economic aspect, cooperation in trade is not restricted only between Muslims. However, anyone can be a business associate. There is no discrimination against people of other faiths or of certain groups.